Is There a Relationship between DNA Methylation and Phenotypic Plasticity in Invertebrates? - Roberts, Steven B.; Gavery, Mackenzie R. (Frontiers in Physiology, 2012)
There is a significant amount of variation in DNA methylation characteristics across organisms. Likewise, the biological role of DNA methylation varies across taxonomic lineages. In some species, particularly invertebrates, there is increasing evidence suggesting that DNA methylation patterns contribute to enhanced phenotypic plasticity. For instance, based on recent studies in Crassostrea gigas, the absence of germline methylation could passively facilitate random variation increasing adaptive potential. Specific mechanisms by which limited methylation may contribute to increased phenotypic plasticity include: allowing access to alternative transcription start sites, sequence mutations, exon skipping, as well as transient methylation. Here we provide a perspective on the potential role of DNA methylation patterning providing advantages in organisms found in highly fluctuating environments. Fundamental differences in DNA methylation landscapes across organisms are discussed including recent research characterizing DNA methylation in invertebrates.